2012
DOI: 10.1039/c2ob25379h
|View full text |Cite
|
Sign up to set email alerts
|

Domino cyclization–alkylation protocol for the synthesis of 2,3-functionalized indoles from o-alkynylanilines and allylic alcohols

Abstract: A practical and efficient protocol for the one-pot synthesis of 2,3-substituted indoles was developed via a palladacycle catalyzed domino cyclization-alkylation reaction involving 2-alkynylanilines and allylic alcohols under mild conditions without any additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Arylboronic acids have also been employed, as in the case of the synthesis of 2,3-diphenylindole ( 139 ), which was obtained by cyclization of 2-alkynyltrifluoroacetanilide 138 catalyzed by Pd(OAc) 2 (5 mol %)/dppp (5 mol %) followed by an in situ cross-coupling with phenylboronic acid, the process being performed in the presence of potassium phosphate under an atmospheric pressure of oxygen, in methanol at 60 °C (Scheme ) . Recently, even allylic alcohols have been used for the incorporation of allyl moieties to the 3-position of 2-substituted indoles when using this 5- endo - dig cyclization …”
Section: Chemicals By Palladium-catalyzed Intramolecular Additions To...mentioning
confidence: 99%
See 1 more Smart Citation
“…Arylboronic acids have also been employed, as in the case of the synthesis of 2,3-diphenylindole ( 139 ), which was obtained by cyclization of 2-alkynyltrifluoroacetanilide 138 catalyzed by Pd(OAc) 2 (5 mol %)/dppp (5 mol %) followed by an in situ cross-coupling with phenylboronic acid, the process being performed in the presence of potassium phosphate under an atmospheric pressure of oxygen, in methanol at 60 °C (Scheme ) . Recently, even allylic alcohols have been used for the incorporation of allyl moieties to the 3-position of 2-substituted indoles when using this 5- endo - dig cyclization …”
Section: Chemicals By Palladium-catalyzed Intramolecular Additions To...mentioning
confidence: 99%
“…147 Recently, even allylic alcohols have been used for the incorporation of allyl moieties to the 3-position of 2-substituted indoles when using this 5endo-dig cyclization. 148 The starting o-alkynylated aniline derivatives for these palladium-catalyzed indole syntheses are frequently prepared from terminal alkynes using the well-known palladiumcatalyzed Sonogashira reaction (see section 6.1). Therefore, it is suitable to in situ generate the o-alkynylated system from a terminal alkyne and an o-halogenated aniline derivative, and further perform the cyclization reaction.…”
Section: Heterocyclesmentioning
confidence: 99%
“…A closely related enantioselective variant of this approach was later proposed by Trost et al using Pd 2 dba 3 ⋅CHCl 3 as the catalyst and 9‐BBN‐C 6 H 13 (105 mol%) as an additive 7c. Pullarkat et al employed a palladacycle catalyst (10 mol%) for the C‐3 allylation of 2‐substituted indoles 7d. Breit et al accomplished the allylation of indoles using the unique concept of self‐assembling palladium phosphane catalysts 7e.…”
Section: Catalysts Screening[a]mentioning
confidence: 99%
“…Due to the substituted indene derivatives widely being used as building blocks for the synthesis of pharmaceutical compounds and functional materials, many methods have been tried to construct these scaffolds. Unfortunately, not like the transition-metal-catalyzed heterocyclization/functionalization, so far it is still difficult to simultaneously introduce different carbon sources to the alkynyl triple bond toward preparing the multi-substituted indene derivatives. Our previous work showed that the (alkenyl)­naphthalene derivatives could be obtained by cycloaromatization of o -(alkynyl)­styrenes in the presence of PdCl 2 as the catalyst under an oxygen atmosphere (Scheme c) .…”
mentioning
confidence: 99%